FORENSIC THANATOLOGY: PRINCIPLES, PROCESSES, AND APPLICATIONS - Saidov Akmal Abdulloevich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic thanatology is a specialized branch of forensic medicine that focuses on the study of death and the processes associated with dying from a medico-legal perspective. This includes determining the cause, manner, and time of death, evaluating postmortem  changes,  and  differentiating  between  antemortem  and  postmortem injuries. This paper provides an overview of the scope, scientific basis, and practical applications of forensic thanatology in modern medico-legal investigations